2018
DOI: 10.1016/j.pan.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of fatty pancreas in Yangzhou, China: A cross-sectional study

Abstract: The prevalence of fatty pancreas in the examined population is approximately 2.7%. Increased age, central obesity and fatty liver disease are independent risk factors for fatty pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 30 publications
0
42
0
5
Order By: Relevance
“…A total of 13 studies reported on the proportion of individuals with NAFPD were eligible. Eight studies provided data on the proportion of individuals with metabolic syndrome in the presence or absence of NAFPD, comprising a total of 36 795 individuals, were included in this analysis. The flowchart of study selection is depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 13 studies reported on the proportion of individuals with NAFPD were eligible. Eight studies provided data on the proportion of individuals with metabolic syndrome in the presence or absence of NAFPD, comprising a total of 36 795 individuals, were included in this analysis. The flowchart of study selection is depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…There were 10 studies reporting on the proportion of DM individuals in the presence or absence of NAFPD. One thousand ninety five individuals had DM in 5550 individuals with NAFPD; 4097 individuals had DM in 43 863 individuals without NAFPD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In non‐obese T2DM patients, a significant association between pancreatic steatosis and atherosclerosis has been reported . In addition, fatty liver is one of the risk factors for fatty pancreas . Infection and autoimmune diseases are also involved in the development of fatty pancreas .…”
Section: What Is Fatty Pancreas?mentioning
confidence: 99%
“…28 In addition, fatty liver is one of the risk factors for fatty pancreas. 29 Infection and autoimmune diseases are also involved in the development of fatty pancreas. 22 Infection by Helicobacter pylori in humans and infection by Coxsackie B viruses in mice have been reported to cause severe pancreatitis and lead to the replacement of damaged acinar cells with adipocytes.…”
Section: Fatty Pancreas-associated Diseasementioning
confidence: 99%